Application of Cognitive Dissonance in Persuasive Communication of Leaders to Education Staff at SMK Negeri 1 Belida Darat - Nadilah; Fera Indasari; M. Miftah Farid (Universitas Muhammadiyah Palu, 2026)
This study aims to determine the application of cognitive dissonance in persuasive communication of leaders in education staff at SMK Negeri 1 Belida Darat. This research is motivated by the difference between the personal beliefs of education personnel and the policies or directions implemented by school leaders, thus causing psychological discomfort that encourages adjustments in attitudes and behaviors. In these conditions, persuasive communication by leaders is an important factor in helping education personnel accept policies and adjust to organizational demands. This study uses a qualitative research method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The informants in this study consisted of school principals, teachers, and education staff at SMK Negeri 1 Belida Darat. Data is analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the application of cognitive dissonance in persuasive communication of leaders can be seen through four indicators, namely the desire for consistency, psychological inconsistency, dissonance driving change, and efforts to achieve consistency. When there is a discrepancy between personal beliefs and school policies, education personnel experience psychological discomfort in the form of doubt, confusion, and decreased morale. However, through persuasive communication that is carried out openly, clearly, and gradually, education personnel are able to adjust and accept the policies implemented. Thus, persuasive communication by leaders plays an important role in reducing cognitive dissonance and encouraging changes in attitudes and consistency in the work of education personnel in the school environment.